New insect assemblage from the early Oligocene in Ningming Basin, Guangxi, China - Wang, Yehao; Nel, André; Cai, Chenyang; Fu, Yanzhe; Liu, Qi; Zeng, Guangchun; Lian, Xinneng; Huang, Diying (Zootaxa, 2025)
The Ningming Basin was characterized by a humid subtropical monsoon climate during the early Oligocene, which supported a rich assemblage of plant and fish fossils. However, the insect fauna from this period has remained poorly documented, with only a single damselfly species formally described. Recent investigations have yielded a distinct collection of insect fossils, comprising at least five orders and represented by 98 specimens, among which ants are the predominant group. In addition, we report four distinct types of herbivory traces and one pathogen‑related damage type on contemporaneous leaves, providing direct evidence of biological interactions. These findings significantly expand the known early Oligocene entomofauna from southern China and enhance our understanding of terrestrial ecosystems under a humid subtropical monsoon regime during this epoch.